Development of Fun Flipbook Activity Media in Improving Numeracy Skills of Grade IV in Elementary Schools - Zunaidah, Farida Nurlaila; Nurmilawati, Mumun; Budiretnani, Dwi Ari (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study is to integrate the values ​​of the ngunggahne beras ritual into the learning process in elementary schools. So that it can determine how deeply students understand the ngunggahne beras ritual in their area. The method used in this study is qualitative by using research instruments in the form of pretest questions and LKPD (Student Worksheets) that have been adjusted to the needs, namely questions related to the ngunggahne beras ritual. The LKPD used had previously been approved for its suitability for use in terms of appearance and questions in the FGD (Forum Group Discussion). The data collection technique was by providing pretest questions at the beginning of learning and questions in the LKPD during the learning process. The data analysis technique was by analyzing the answers to each question on the pretest and questions in the LKPD. Based on the analysis that has been carried out, it is known that there is a difference in knowledge of the values ​​of ngunggahne beras before and after it is explained. It is hoped that after understanding the values ​​of the ngunggahne beras ritual, the next generation can preserve the original culture in their area.